Implementasi Manajemen Hubungan Masyarakat di MI Muhammadiyah Ponorogo - Bambang Wahrudin; Wawan Kusnawan; Mushlih Candrakusuma (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Community relations are an important pillar in the development of institutions, including the development of madrasas. Public relations management is needed as an effort to create harmonious relations between institutions and the community. Various models of public relations that have been put forward by experts include the Press Agentry model, Public Information and the Two-way Asymmetrical Model which are models that are often used in building institutional and community relations. Through qualitative research with a case study approach and data collection carried out through participant observation, in-depth interviews and documentation of data on community relations were processed using data and source triangulation. The results obtained from this study are that MI Muhammadiyah 13 Pijeran applies a public relations model through the press agentry model with various forms of programs and activities including routine recitations, year-end activities, performing arts and others. These programs and activities are carried out by MI Muhammadiyah 13 Pijeran in order to strengthen relations with the community.